A novel tool to detect behavioural symptoms in ALS. Issue 3 (1st June 2014) - Mioshi, Eneida; Hsieh, Sharpley; Caga, Jashelle; Ramsey, Eleanor; Chen, Kelly; Lillo, Patricia; Simon, Neil; Vucic, Steve; Hornberger, Michael; Hodges, John R.; Kiernan, Matthew C.
Abstract: There is need for a valid, sensitive and short instrument capable of detecting and quantifying behavioural changes in ALS, which can be utilized in clinical and research settings. This study aimed to 1) develop and validate such an instrument; 2) verify the most common behavioural symptoms; and 3) investigate longitudinal changes over a six-month period. Two hundred and nineteen patients were included. The development sample ( n = 140) was used to determine the most appropriate items to include in the new tool, the Motor Neuron Disease Behavioural Instrument (MiND-B)1, via a data-driven approach. An independent sample ( n = 79) validated the tool. A more comprehensive sample ( n = 50, sub-classified into ALS and ALS plus) was utilized to verify if the MiND-B could detect ALS plus patients. Finally, 20 ALS patients completed the MiND-B after a six-month period. Apathy, disinhibition and stereotypical behaviour were all found to be very common symptoms in ALS occurring in 75%, 66% and 58%, respectively, of cases. Notably, the MiND-B could identify ALS plus patients without standard cognitive assessments. In conclusion, the MiND-B tool can detect patients with ALS plus reliably, by means of questions to the informant. This test could enable ALS centres to evaluate non-motor symptoms and adapt management and decision-making approaches as necessary.